A school-based program to prevent depressive symptoms and strengthen well-being among pre-vocational students (Happy Lessons): protocol for a cluster randomized controlled trial and implementation study - Marieke Rombouts; Elisa L. Duinhof; Marloes Kleinjan; Jannis T. Kraiss; Laura Shields-Zeeman; Karin Monshouwer (BMC, 2022)
Abstract Background Depression is one of the leading causes of illness and disability among young people. In the Netherlands, one in twelve Dutch adolescents has experienced depression in the last 12 months. Pre-vocational students are at higher risk for elevated depressive symptoms. Effective interventions, especially for this risk group, are therefore needed to prevent the onset of depression or mitigate the adverse long-term effects of depression. The aim of this study is to examine the effectiveness and implementation of a school-based program Happy Lessons (HL), that aims to prevent depression and promote well-being among pre-vocational students. Methods A cluster randomized controlled trial (RCT) with students randomized to HL or to care as usual will be conducted. Pre-vocational students in their first or second year (aged 12 to 14) will participate in the study. Subjects in both conditions will complete assessments at baseline and at 3- and 6-months follow-up. The primary outcome will be depressive symptoms using the Center for Epidemiologic Studies Depression Scale (CES-D) at 6-months follow-up. Secondary outcomes are well-being using the Warwick-Edinburgh Mental Well-Being Scale (WEMWBS) and life satisfaction (Cantril Ladder) measured at 6-months follow-up. Alongside the trial, an implementation study will be conducted to evaluate the implementation of HL, using both quantitative and qualitative methods (interviews, survey, and classroom observations). Discussion The results from both the RCT and implementation study will contribute to the limited evidence base on effective school-based interventions for the prevention of depression and promotion of well-being among pre-vocational adolescents. In addition, insights from the implementation study will aid identifying factors relevant for optimizing the future implementation and scale-up of HL to other schools and contexts. Trial registration This study was registered on 20 September 2021 in the Dutch Trial Register ( NL9732 ).